Gamification and Role Play: Two Combined Teaching Strategies for Developing Students' Speaking Skills - Safitri, Ni Putu Dianita; Tari, Nirmala (Jurnal Manajemen Pelayanan Hotel, 2022)
The education sector is one of the sectors seriously affected by the COVID -19 pandemic outbreak. The learning process changed from having many social interactions to being seated behind a screen for hours. Online learning connects students to a different learning experience. This has become a challenging task f or educators to make the students engaged and motivated through an online learning process; therefore, it requires the educator to discover new teaching strategies. The use of digital platforms for online learning has grown the students' interest exponentially. The educators design the learning material through games. One of the digital platforms used to maximize students' enjoyment and engagement is gamification. In this new normal, the learning process has immediately switched to offline classes. Educators need to provide an active learning activity, especially in teaching speaking. Role p lay is a common technique used to promote active learning and develop students' speaking skills. However, students need fun activities using their mobile phones, and gamification is the solution. The purpose of the study was to analyze the implementation of two combined strategies (gamification and role play) in teaching speaking for developing university students' speaking skills. There were 16 students involved in this study. The design of the study used an embedded mixed method which was mainly in the f orm of a qualitative study but supported by a quantitative data analysis. The study shows that the use of gamification and role play has a beneficial contribution to students' speaking skills. Keywords: Gamification, Role Play. Speaking Skill